The aspectual form of the Russian verb as a means of value categorization in proverbial speech - Ruzieva, Zilola Mustafaevna (The Lingua Spectrum, 2026)
The article studies the axiological potential of the grammatical category of aspect in the Russian verb on the material of Russian proverbs. The study assumes that evaluation in proverbs is produced not only by lexical units such as good, bad, labour, trouble or wisdom, but also by the aspectual organization of verbal action. The material includes a working sample of 72 Russian proverbs selected from classical paremiographic sources by V.I. Dal, V.P. Zhukov and the collection edited by V.P. Anikin. The analysis distinguishes three groups: proverbs dominated by the imperfective aspect, proverbs dominated by the perfective aspect, and mixed aspectual models. The imperfective aspect mainly verbalizes norm, habit, recurrence and socially approved duration of behaviour. The perfective aspect highlights result, boundary, consequence and moral outcome. The findings specify the value semantics of Russian proverbs and may be useful for aspectological and linguocultural research.